Career Break, Not a Brake on Career: A Study of the Reasons and Enablers of Women's Re-entry to Technology Careers in India. Issue 2 (May 2021) - Singh, Swati; Vanka, Sita
Career re-entry of women in the technology sector remains an unexplored area. With the increasing focus of information technology (IT) organisations to attract, retain and promote women at the workplace, career re-entry among women professionals' merits attention. The purpose of this study is to investigate the reasons and enablers of career re-entry among women who plan a re-entry in the IT sector in India. This study employed a qualitative research method and used interviews as a tool for data collection. Data collected through the interviews of re-entry women ( n = 28) was analysed with the help of qualitative analysis software ATLAS.ti. Further, text analysis was also performed through Voyant tools. Findings suggest that a strong career identity, a high level of work centrality and an urge to regain financial independence motivated women to return to IT careers. Findings revealed seven distinct enablers of career re-entry. Based on this finding, a model of the support ecosystem is discussed that presents an intricate relationship between the enablers of career re-entry, support ecosystem and career resumption. Moreover, findings indicate that an active agency of women, a support ecosystem and favourable life events lead to career re-entry. Managerial and theoretical implications of findings are discussed. The article concludes with limitations and future research agenda.